2020
DOI: 10.3390/pharmacy8020057
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Medication Review in General Practice by an Interdisciplinary Team: A thorough but Laborious Method to Address Polypharmacy among Elderly Patients

Abstract: Polypharmacy increases the risk of hospitalization but may be reduced by medication review. The study objective is to describe and evaluate a method for conducting medication review in general practice by an interdisciplinary medication team of pharmacists and physicians—in this case conducted by a team from the Department of Clinical Pharmacology—based on information concerning medication, diagnosis, relevant laboratory data and medical history supplied by the general practitioner. We discussed the medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Despite best-practice guidelines, a US study documented limited PIM discontinuation rates, for older adults with limited life expectancy [ 26 ]. Similarly, deprescribing interventions, such as medication reviews, are considered unlikely to be incorporated into daily practice [ 27 ]. Researchers have called for an increased focus on implementation science to bridge the “research-to-practice gap”, which may increase deprescribing engagement in clinical practice by, for example, tailoring interventions to the long-term care environment [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite best-practice guidelines, a US study documented limited PIM discontinuation rates, for older adults with limited life expectancy [ 26 ]. Similarly, deprescribing interventions, such as medication reviews, are considered unlikely to be incorporated into daily practice [ 27 ]. Researchers have called for an increased focus on implementation science to bridge the “research-to-practice gap”, which may increase deprescribing engagement in clinical practice by, for example, tailoring interventions to the long-term care environment [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could be achieved in different ways, but it should include a clear understanding from both parts of what to expect when deprescribing and which symptoms the nursing home staff needed to be observant of as well as how to handle uncertainties. One of the experts, the clinical pharmacist with experience in deprescribing studies in Danish nursing homes, suggested using the Neuropsychiatric Inventory – nursing home version (NPI-NH) [ 26 , 51 ]. The symptom assessment scale was considered by both nursing home staff and GPs as a means to ensure a common language concerning what was relevant to report from nursing home staff to the GP.…”
Section: Resultsmentioning
confidence: 99%
“…require a greater amount of therapy. Therefore, in the presence of a mutation of cytochrome Р450, on which most processes of drug biotransformation occur, there is a greater risk of the development of adverse reactions against the background of polypharmacy (Larock et al 2014;Page et al 2016;Dalin et al 2020;Foley et al 2020;Martinez et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, it is very important to study the problem of polypharmacy in the Russian population. To solve a number of problems, which are defined by the Procedures for providing medical care in clinical pharmacology, a developed multi-component system of managing pharmacotherapy risks should be used (Khokhlov and Lisenkova 2003;Rakov et al 2003;Magro et al 2012;Starodubov et al 2012;Dalin et al 2020).…”
Section: Introductionmentioning
confidence: 99%